Industrial Design Protection in Indonesia and the European Union: A Comparative Analysis of Legal Frameworks and WIPO-Based Dispute Indicators - Moh. Mustakim Fauzan; Dewi Sulistianingsih (Al-Risalah, 2026)
This study examines industrial design protection through a comparative legal analysis between Indonesia and the European Union by integrating normative legal assessment with empirical indicators derived from the World Intellectual Property Organization (WIPO) IP Statistics Data Center and related WIPO statistical reports during the 2019–2024 period. The research employs a normative-comparative juridical method using statute and comparative approaches to analyze Law No. 31 of 2000 on Industrial Design and Council Regulation (EC) No. 6/2002 on Community Designs. The empirical indicators utilized include industrial design filing activity, Hague System utilization, and institutional enforcement trends related to industrial design protection. The findings demonstrate that Indonesia’s industrial design regime is formally aligned with international standards but remains procedurally rigid and institutionally fragmented, particularly regarding judicial specialization, digital enforcement adaptation, and preventive protection mechanisms. In contrast, the European Union has developed a more integrated and adaptive system supported by harmonized regulations, specialized institutions, and broader utilization of international registration systems. The study further reveals that differences in enforcement effectiveness are strongly influenced by institutional integration and accessibility rather than merely normative legal conformity. Therefore, strengthening industrial design protection in Indonesia requires operational institutional reforms, digital administrative integration, and expansion of international protection mechanisms to bridge the gap between formal legal regulation and practical enforcement effectiveness.